1991
DOI: 10.1152/ajpcell.1991.260.1.c122
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cellular volume in rabbit ventricular myocytes: bumetanide, chlorothiazide, and ouabain

Abstract: Video microscopy was used to study the regulation of cell volume in isolated rabbit ventricular myocytes. Myocytes rapidly (less than or equal to 2 min) swelled and shrank in hyposmotic and hyperosmotic solutions, respectively, and this initial volume response was maintained without a regulatory volume decrease or increase for 20 min. Relative cell volumes (normalized to isosmotic solution, 1T) were as follows: 1.41 +/- 0.01 in 0.6T, 1.20 +/- 0.04 in 0.8T, 0.71 +/- 0.04 in 1.8T, and 0.57 +/- 0.03 in 2.6T. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
124
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 19 publications
26
124
2
Order By: Relevance
“…First, if BUM blocked CI-and K + efflux, it should increase cell volume. As shown here and previously (Clemo and Baumgarten, 1991a;Drewnowska and Baumgarten, 1991), BUM significantly decreased cell volume. Second, BUM decreases intracellular CI-activity (Baumgarten and Duncan, 1987;Liu et al, 1987).…”
Section: Does Cgmp Reduce Cell Volume By Inhibiting Na+/k+/2cl -Cotrasupporting
confidence: 91%
See 1 more Smart Citation
“…First, if BUM blocked CI-and K + efflux, it should increase cell volume. As shown here and previously (Clemo and Baumgarten, 1991a;Drewnowska and Baumgarten, 1991), BUM significantly decreased cell volume. Second, BUM decreases intracellular CI-activity (Baumgarten and Duncan, 1987;Liu et al, 1987).…”
Section: Does Cgmp Reduce Cell Volume By Inhibiting Na+/k+/2cl -Cotrasupporting
confidence: 91%
“…3 B). Previously we showed that the volume of rabbit myocytes remains stable in hypotonic solutions rather than THE JOURNAL OF GENERAL PHYSIOLOGY " VOLUME 100 " 1992 undergoing a regulatory volume decrease (Drewnowska and Baumgarten, 1991). To eliminate the chance that BUM-induced shrinkage prevented ANF's effect, the study was repeated in cells preswollen in 0.8T media for 10 min.…”
Section: Cgmp Blocks Na+ /K+ /2cl -Cotransportmentioning
confidence: 99%
“…A combination of commercial (SigmaScan Pro, SPSS; Chicago, IL) and custom programs were used to determine cell width, length, and the planar area of the image. Changes in cell width and thickness are proportional (9). Taking each cell as its own control, relative cell volume was calculated as vol t/volc ϭ (areat ϫ widtht)/(areac ϫ widthc), where t and c refer to test (e.g., 0.6T) and control (1T) solutions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The calculated values are independent of assumptions regarding the geometric shape of the cross section of the myocyte as long as the shape does not change. These methods provide estimates of relative cell volume that are reproducible to Ͻ1% (7,9).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to APD, the mechanism of hypoxic cell swelling is not completely understood. Although the ATP-dependent Na + /K + pump was suppressed on incubation with 1 μM ouabain, no significant change occurred in the cell volume of rabbit ventricular cells (5). A recent report revealed that the coordinated action of the ATP-dependent plasma membrane calcium pump and Na + /Ca 2+ exchanger substitutes for the Na + /K + pump in extruding Na + from the cells during ouabain exposure (16).…”
mentioning
confidence: 98%